Strategi Komunikasi Branding Kawasan Ekonomi Khusus Mandalika dalam Membangun Citra Destinasi Investasi Pariwisata dan Infrastruktur - Limarandani, Ni Putu; Sulitya, Inka; Mutiah, Tuty (Warta Ikatan Sarjana Komunikasi Indonesia, 2025)
Abstract - The Mandalika Special Economic Zone (SEZ) is one of Indonesia’s Super Priority Tourism Destinations (SPTD), strategically developed to drive economic growth through the tourism and infrastructure sectors. In this context, branding communication strategy plays a crucial role in shaping a positive image of the area as a competitive investment destination, both nationally and internationally. This study aims to analyze the branding communication strategies implemented by the Mandalika SEZ management and evaluate their effectiveness in building a favorable perception among investors. Employing a qualitative approach with a case study method, data were collected through in-depth interviews with various stakeholders, including SEZ managers (ITDC), local and central governments, investors, academics, communication practitioners, local communities, media, and influencers. Field observations and document studies were also conducted to enrich the analysis. The findings reveal that despite the use of various media and promotional channels, the current communication strategies still face significant challenges, such as message inconsistency, generalized narratives, lack of focus on return on investment (RoI), minimal authentic local storytelling, and limited stakeholder involvement in communication planning. A more participatory, collaborative, and contextual communication approach is needed, emphasizing message personalization for target investors and strengthening local culture-based storytelling as a distinctive element. Direct investor involvement in communication campaigns can also enhance credibility and promotional reach. Strategic recommendations include message consistency, audience segmentation, integration of local values in branding, and cross-sector synergy in formulating communication strategies. With these improvements, Mandalika SEZ has the potential to become a globally competitive and sustainable tourism and infrastructure investment destination.Keywords: Communication Strategy, Branding, Mandalika SEZ, Investment, Tourism, Infrastructure Abstrak - Kawasan Ekonomi Khusus (KEK) Mandalika merupakan salah satu Destinasi Pariwisata Super Prioritas (DPSP) yang difokuskan untuk mendorong pertumbuhan ekonomi melalui sektor pariwisata dan infrastruktur. Dalam konteks ini, strategi komunikasi branding memegang peran krusial dalam membentuk citra positif kawasan sebagai destinasi investasi yang kompetitif, baik di tingkat nasional maupun internasional. Penelitian ini bertujuan menganalisis strategi komunikasi branding yang diterapkan oleh pengelola KEK Mandalika serta mengevaluasi efektivitasnya dalam membangun persepsi positif di kalangan investor. Menggunakan pendekatan kualitatif dengan metode studi kasus, data dikumpulkan melalui wawancara mendalam dengan berbagai pemangku kepentingan, termasuk pengelola kawasan, pemerintah daerah dan pusat, investor, akademisi, praktisi komunikasi, masyarakat lokal, serta media dan influencer. Observasi lapangan dan studi dokumentasi turut dilakukan untuk memperkaya analisis. Hasil penelitian menunjukkan bahwa meskipun berbagai media dan saluran promosi telah digunakan, strategi komunikasi yang ada masih menghadapi tantangan serius, antara lain ketidakkonsistenan pesan, generalisasi narasi, kurangnya fokus pada return of investment (RoI), minimnya narasi lokal yang autentik, serta rendahnya partisipasi stakeholder dalam perencanaan komunikasi. Diperlukan pendekatan komunikasi yang lebih partisipatif, kolaboratif, dan kontekstual, dengan penekanan pada personalisasi pesan kepada investor sasaran dan penguatan storytelling berbasis budaya lokal sebagai elemen pembeda. Keterlibatan langsung investor dalam kampanye komunikasi juga dapat meningkatkan kredibilitas dan jangkauan promosi. Rekomendasi strategis meliputi konsistensi pesan, segmentasi audiens, integrasi nilai-nilai lokal dalam branding, serta sinergi lintas sektor dalam perumusan strategi komunikasi. Dengan demikian, KEK Mandalika berpotensi menjadi destinasi investasi pariwisata dan infrastruktur yang berkelanjutan dan berdaya saing global. Kata kunci: Strategi Komunikasi, Branding, KEK Mandalika, Investasi, Pariwisata, Infrastruktur